2015
DOI: 10.1038/npp.2015.331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Striatal Dopamine D2/D3 Receptors in Methamphetamine Users during Behavioral Treatment

Abstract: Methamphetamine use disorder is associated with striatal dopaminergic deficits that have been linked to poor treatment outcomes, identifying these deficits as an important therapeutic target. Exercise attenuates methamphetamine-induced neurochemical damage in the rat brain, and a preliminary observation suggests that exercise increases striatal D2/D3 receptor availability (measured as nondisplaceable binding potential (BP ND )) in patients with Parkinson's disease. The goal of this study was to evaluate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 52 publications
4
75
1
1
Order By: Relevance
“…Although several studies have shown causal links for short-term activity interventions and DRD2 receptors in animals, humans with Parkinson’s Disease, and human methamphetamine users (Fisher et al, 2013; Robertson et al, 2016; Vuckovic et al, 2010), our data do not directly show that physical activity causally ameliorates DRD2 loss in normal aging. It may be that individuals with higher DRD2 in the ventral striatum, an area associated with reward functions, are more motivated to be physically active as they age.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Although several studies have shown causal links for short-term activity interventions and DRD2 receptors in animals, humans with Parkinson’s Disease, and human methamphetamine users (Fisher et al, 2013; Robertson et al, 2016; Vuckovic et al, 2010), our data do not directly show that physical activity causally ameliorates DRD2 loss in normal aging. It may be that individuals with higher DRD2 in the ventral striatum, an area associated with reward functions, are more motivated to be physically active as they age.…”
Section: Discussioncontrasting
confidence: 93%
“…Intriguingly, exercise training was observed to increase striatal DRD2 receptor availability in humans with Parkinson’s disease and methamphetamine users (Fisher et al, 2013; Robertson et al, 2016). However, although aging, Parkinson’s disease, methamphetamine use and MPTP neurotoxicity all impact dopamine functions, the specificity of their effects on the dopamine system differs significantly.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to enhance striatal D2/3 BP nd is through exercise training, as has been suggested for patients with stimulant use disorder (Robertson et al, 2015). Exercise was proposed as a smoking-cessation aid long ago, and there are some reports of benefits from exercise in reducing tobacco consumption, albeit with limited evidence of long-term benefit (Ussher et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Future prospective studies may include collecting those measures as well as investigating exercise interventions to examine D 2/3 R transformations as BMI decreases. In fact, one study using [ 18 F]fallypride has recently demonstrated that exercise intervention for 8 weeks, compared with psychoeducation, normalized lower striatal D 2/3 Rs in humans with methamphetamine-use disorder (Robertson et al, 2015). Second, although research participants were gender-and age-matched in the primary between-group comparisons, the cohort for the secondary correlational analyses was heavily dominated by males (33 males vs 9 females); thus, further correlational analyses confirming our findings are warranted in a gender-balanced cohort.…”
Section: Discussionmentioning
confidence: 99%